Science, Art and Christian Identity - Lombaerts, Herman (Acta Paedagogica Vilnensia, 2003)
This article intends to explore briefly the relationship between art, science and the Christian identity. Art and science are presented as activities where the human person owns his/her autonomy in the effort to explain the world, the universe and life in all its aspects. The Christian identity is to be understood as a reflective and committed interpretation of the changes in awareness and self-representation as the result of both, the scientific insights and the artistic expressions. Firstly, the author argues that scientific findings stimulate the believers to clarify their religious thinking and attitudes and to deepen the dynamic nature of a religious identity. Secondly, it is argued that also art transgresses boundaries of (religious) self-representation, introduces people into new sensitivity and awareness, and inspires a creative relationship with the self-revealing God. The author refers to the historical evolution and to contemporary events to illustrate the dynamic interaction between sciences, art and the Christian identity.